Corneal Stiffness and Its Relationship With Other Corneal Biomechanical and Nonbiomechanical Parameters in Myopic Eyes of Chinese Patients. Issue 7 (July 2018) - Zhang, Yaohua; Wang, Yan; Li, Liuyang; Dou, Rui; Wu, Wenjing; Wu, Di; Jhanji, Vishal
Abstract : Purpose: To investigate corneal stiffness and analyze its possible influence on other corneal biomechanical and nonbiomechanical parameters in myopic eyes of Chinese patients. Methods: A total of 387 healthy (right) myopic eyes were included in this study. Corneal visualization Scheimpflug technology was used to measure the corneal stiffness parameter at the first applanation (SP-A1), deformation amplitude ratio at 1.0 and at 2.0 mm, biomechanically corrected intraocular pressure (bIOP), and corneal deformation parameters during the first applanation (A1: A1-time, A1-length, and A1-velocity), second applanation (A2; A2-time, A2-length, and A2-velocity), and highest concavity (HC; HC-time, HC-radius, HC deformation amplitude, and HC peak distance). The Pentacam was used to evaluate central corneal thickness, mean corneal curvature (Km), anterior corneal central elevation, and corneal asphericity (Q value) of the anterior cornea. Results: The mean SP-A1 and bIOP values were 90.46 ± 15.39 mm Hg/mm and 13.5 ± 1.85 mm Hg, respectively. The SP-A1 increased with age (β = 0.41 [95% CI, 0.28%–0.54%]; P < 0.0001). Corneal stiffness was positively correlated with central corneal thickness, uncorrected intraocular pressure, and bIOP and was also significantly correlated with all corneal deformation parameters ( P < 0.05), except A1-length, HC-time, and HC peak distance. Corneal stiffness was negatively correlated with central corneal elevation of the anterior surface (r = −0.124, P = 0.014) and mean corneal curvature (r = −0.114, P = 0.025) and positively correlated with the Q value of the anterior surface (r = 0.109, P = 0.032). Conclusions: Corneal stiffness increased with age. Stronger corneal stiffness may be related to flattening of the cornea and higher intraocular pressure.